Causation and climate change litigation: ‘bridge too far’? - Wilde, Mark (Austrian Law Journal, 2021)
The phenomenon of ‘climate change litigation’ has come to the fore in recent years as campaigners and activists have become increasingly frustrated at a perceived lack of action on the part of the international community and individual states in terms of getting to grips with the climate change problem. Existing legal mechanisms available to private parties and other bodies, such as non-governmental organizations (NGOs) have been used as a means of endeavouring to hold governments and polluters to account for the effects of climate change. The physical impact of climate change on life and property has been thrown into sharp relief by floods and wildfires in all parts of the globe. One aspect of climate change litigation focuses on the role that tort might play in attempting to secure compensation for at least part of such losses. No one would pretend that actions of this nature can actually solve the problem, but they may serve to shame polluters and so forth by establishing an actual link between their activities and the tangible consequences of climate change. However, such actions raise formidable causation difficulties which have, until recently, rendered such claims outlandish and highly speculative. Nevertheless, developments in extreme weather event attribution may be about to reduce the conceptual and theoretical barriers to bringing such claims. In this article it is argued that, from a UK perspective, existing causality tests may be capable of accommodating such evidence, although, one must be aware of countervailing policy considerations which may inhibit the courts from adopting such an approach.